Ru-TiO2 semiconducting nanoparticles for the photo-catalytic degradation of bromothymol blue - Kulkarni, R. M.; Malladi, R. S.; Hanagadakar, M. S.; Doddamani, M. R.; Santhakumari, B.; Kulkarni, S. D. (Journal of Materials Science-Materials in Electronics, 2016)
Photo-catalytic degradation of bromothymol blue (BTB) in an aqueous medium by Ru-TiO2 using UVC (254 nm) irradiation was investigated for a pH range of 4.0-8.0. The liquid impregnation method was used to synthesize 0.2, 0.4 and 0.8 % ruthenium doped TiO2 (Ru-TiO2) nanoparticles. The characterizations of resulting nanoparticles were done using X-ray diffraction, scanning electron microscopy, fourier transform infrared spectroscopy, transmission electron microscopy (TEM) and energy dispersive X-ray spectroscopy analysis. The crystallite sizes of doped and undoped nanoparticles were determined from X-ray diffraction spectra using Scherrer equation. The average crystallite size of undoped TiO2 was found to be 17.00 nm, whereas the crystallite sizes of 0.2, 0.4 and 0.8 % Ru-TiO2 were 16.67, 15.70 and 14.40 nm respectively. The TEM images confirm the particle sizes to be 10-40 nm. Pseudo-first order rate constants (k(obs)) determined were found to decrease with increase in pH. The effect of BTB Concentration, catalyst dosage, a percentage of doping of photo catalyst, pH and UV light intensity of BTB on the degradation rate were also examined.